Theoretical-methodological and contrastive study of paremiological competence in mother tongue and foreign language in a university setting - M.ª, Ferreiro Dolores Asensio; Sciutto, Virginia (Romanica Olomucensia, 2024)
The acquisition of paremiological competence (PC) in a foreign language (FL) is always challenging because of the multitude of factors that affect its learning, mainly structural, cultural, and terminological factors. This is an issue that has received little attention in the specialised literature and therefore requires the establishment of adequate theoretical and methodological foundations through rigorous studies that define the lines of action necessary to address the treatment of these units in the FL class. This study sets out the state of the art of this phenomenon, carrying out a geographical contrastive analysis based on the creation of a corpus (COREPUM). The aim is to carry out a contrastive analysis in a double sense: on the one hand, to determine the level of CP in the mother tongue (MT) of the groups of participating informants, made up of university students from Spain and Italy, and, on the other hand, to analyse the level of CP in the first FL of each of these groups (French for the students from Spain and Spanish for the students from Italy). This is a preliminary empirical study which opens the way for future work to address and analyse possible aspects of the problem that is raised, with a view to proposing solutions to improve communicative competence in multilingual contexts.
Keywords: active and passive paremiological competence; mother tongue; foreign language acquisition; corpus linguistics; contrastive analysis